Crear nuestra propia munda: The stakes of space appropriation by lesbians in Mexico City - Yasmine Tuffy (Cahiers des Amériques Latines)
The appropriation of space has historically served as an important tool for the visibilisation of women and queer peoples. Reclaiming space has not only enabled queers to normalise their existence in some urban contexts, but it has also been the basis for the construction of collective identities, which in turn nourish political vindication. This article seeks to cast light upon some of the material aspects of LGBTQI+ collective action from the vantage point of the use of space by lesbians living in Mexico City. Drawing on qualitative data from semi-structured interviews and participant observation, it discusses dynamics linked to spatial segregation, lesbians’ experiences of gay spaces, and the ways in which space constitutes both a stake and a resource for lesbian political mobilisation.